Founder, Civilizer and Leader: Vergil's Evander and his Role in the Origins of Rome - Sophia Papaioannou (Mnemosyne, 2003)
Contrary to the two other major Augustan writers who discussed the origins of Rome, Vergil's Roman prehistory centers on the presence of Evander. An involuntary exile from the East (Greek Arcadia) who settled in Latium and instilled civilization and laws among the Italians, Evander is a duplicate of Aeneas, a cultural ancestor and a model of leadership. Aeneas is instructed by the deities of Italy (Tiberinus) to pay a visit to Pallanteum, Evander's capital and the primordial site of Rome, in order to learn about the past and receive instructions about the future. His tour of proto-Rome, led by Evander, carries Aeneas through a series of monuments that span through Rome's entire history. Aeneas is guided to follow Evander's example, and Vergil, urging reevaluation of widespread anti-Hellenic prejudices, prominently underscores the seminal contribution of Greece to the cultural and political origins of Rome.